Comparison of the Growth and Production of Carps in Polyculture Ponds with Supplemental Feed using Rice Straw and Kanchi as Substrates - Rai, S.; Yi, Y.; Wahab, Md.A.; Bart, A.N.; Diana, J.S. (Our Nature, 2011)
An experiment was carried to compare the performance of rice straw and kanchi in carp polyculture ponds with supplemental feed. The experiment included two treatments in triplicates: a) rice straw substrate (3x625 kgha-1) with supplemental feeding and b) kanchi substrate (390 kanchi pond-1) with supplemental feeding. Fingerlings (n=40) of rohu, Labeo rohita (23.3±0.5 g), catla, Catla catla (26.0±0.6 g), mrigal, Cirrhinus mrigala (25.4±0.7 g), common carp, Cyprinus carpio (28.5±1.9 g) and silver carp, Hypophthalmychthys molitrix (32.1±1.3 g) were stocked at 3:2:2:2:1 ratio. Fish growth and weight gains did not vary between the rice straw and the kanchi treatment except in catla (P>0.05). Daily and total weight gains of catla was 48 and 32% higher in the kanchi treatment than in the rice straw treatment (P<0.05). However, the rice straw treatment gave more profit than the kanchi treatment. Based on fish production and gross margin, the rice straw treatment seems better for resource-poor farmers. DOI: 10.3126/on.v8i1.4316